Impact of precipitation intermittency on NAO-temperature signals in proxy records - M. Casado; P. Ortega; V. Masson-Delmotte; C. Risi; D. Swingedouw; V. Daux; D. Genty; F. Maignan; O. Solomina; B. Vinther; N. Viovy; P. Yiou (Climate of the Past, 2013)
In mid and high latitudes, the stable isotope ratio in precipitation is driven by changes in temperature, which control atmospheric distillation. This relationship forms the basis for many continental paleoclimatic reconstructions using direct (e.g. ice cores) or indirect (e.g. tree ring cellulose, speleothem calcite) archives of past precipitation. However, the archiving process is inherently biased by intermittency of precipitation. Here, we use two sets of atmospheric reanalyses (NCEP (National Centers for Environmental Prediction) and ERA-interim) to quantify this precipitation intermittency bias, by comparing seasonal (winter and summer) temperatures estimated with and without precipitation weighting. We show that this bias reaches up to 10 °C and has large interannual variability. We then assess the impact of precipitation intermittency on the strength and stability of temporal correlations between seasonal temperatures and the North Atlantic Oscillation (NAO). Precipitation weighting reduces the correlation between winter NAO and temperature in some areas (e.g. Québec, South-East USA, East Greenland, East Siberia, Mediterranean sector) but does not alter the main patterns of correlation. The correlations between NAO, δ 18 O in precipitation, temperature and precipitation weighted temperature are investigated using outputs of an atmospheric general circulation model enabled with stable isotopes and nudged using reanalyses (LMDZiso (Laboratoire de Météorologie Dynamique Zoom)). In winter, LMDZiso shows similar correlation values between the NAO and both the precipitation weighted temperature and δ 18 O in precipitation, thus suggesting limited impacts of moisture origin. Correlations of comparable magnitude are obtained for the available observational evidence (GNIP (Global Network of Isotopes in Precipitation) and Greenland ice core data). Our findings support the use of archives of past δ 18 O for NAO reconstructions.